Cantas Gagal Clinic for soil engineering / Khairul Afinawati Hashim … [et al.] - Hashim, Khairul Afinawati (Unit Penerbitan PKAPP, 2024)
The ‘Cantas Gagal Clinic’ program was held in early December 2023 at the Dewan Seminar. It involved 107 Part 5 students from the Diploma in Civil Engineering (CEEC110) and four instructors from Pengajian Kejuruteraan Awam, UiTM Cawangan Pulau Pinang. The main objective of this program was to enhance the teaching and learning experience for the course code ECG353 (Soil Engineering) and improve the achievement of Program Outcomes (PO) for PO1 and PO3. To achieve these objectives, the program provided a platform for students to prepare for the upcoming test in midDecember 2023 and the final examination in late January 2024. Prior to the program, students were given module exercises based on previous final examination questions to complete. During the program, the instructors discussed answering techniques and provided solutions for the module exercises. This approach allowed students to familiarize themselves with the exam format, time constraints, and type of questions they may encounter in tests and final examinations. According to the Continuous Quality Improvement (CQI) report in March 2024, the performance of the PO for this course improved, and the failure rates also decreased. Therefore, it is recommended that this program be continued in the future.